Immunoregulative coating for scarless healing in anterior cruciate ligament reconstruction - Shuang Wang; Chao Xu; Yuanman Yu; Jie Li; Tianwu Chen; Jing Wang; Changsheng Liu (Bioactive Materials)
Polyethylene terephthalate (PET) artificial ligaments are widely used in anterior cruciate ligament (ACL) reconstruction due to their high tensile strength. However, bone tunnel enlargement around PET ligaments poses a risk for surgical failure. PET's inert surface, lower bioactivity, and mechanical abrasion trigger an M1 macrophage-mediated inflammatory response, leading to excessive, disorganized scar tissue. This scar tissue creates a space-occupying effect at the interface, obstructing graft-bone integration and contributing to bone tunnel enlargement. To address this issue, we developed a multi-layered immune-regulating hydrogel coating for scar-free PET-bone integration. Comprising gelatin methacrylate (GelMA), polyethyleneglycol diacrylate (PEGDA), and sulfated polysaccharide (SCS), the hydrogel forms a hydrogen-bonded lubricating layer to reduce friction. The sustained release of SCS also down-regulates M1 macrophage polarization, inhibiting early scar formation. By eliminating the space-occupying effect of scar tissue, SCS subsequently promotes M2 macrophage polarization. This shift releases endogenous factors that enhance blood vessel formation and new bone growth, ultimately achieving high-quality graft-bone integration. The application of this multi-layered, inflammation-modulating hydrogel coating not only removes scar tissue barriers but also improves graft-bone integration through enhanced angiogenesis and osteogenesis. Moreover, it avoids the overuse of exogenous growth factors and potential complications, offering a more convenient and feasible therapeutic strategy.